PELESTARIAN BUDAYA LOKAL SEBAGAI BENTUK IMPLEMENTASI ILMU SOSIAL DAN BUDAYA DASAR DALAM KEHIDUPAN MASYARAKAT - Corry Restuina; Maelisa Putri Damanik; Maria Gabriela Tarihoran; Cherly Br Tarigan; Parida Paskah Purba; Cinthya O Lumban Tungkup; Gerarda Riris Marito Simamora; Rosmeika Sitompul (FKIP Universitas Alwashliyah Medan, 2026)
Preserving local culture is a strategic step in maintaining national identity amidst the rapidly evolving tides of globalization, modernization, and digitalization, particularly in the 2024–2025 period. Basic Social and Cultural Sciences (BSCS) plays a crucial role in fostering public awareness of the social and cultural values ​​that exist and thrive in their environment. Modern developments pose serious challenges to local culture, such as shifting values, weakening cultural identity, and diminishing awareness among the younger generation about regional cultural heritage. If these conditions are not balanced with ongoing preservation efforts, national identity could potentially suffer degradation. This study aims to examine the relevance of ISCS to local cultural preservation efforts and the role of the community, educational institutions, and social communities in maintaining cultural sustainability. The research method used is a qualitative method with a descriptive approach through literature review and social observation of cultural phenomena in the community. The results of the study indicate that preserving local culture not only functions as an effort to preserve cultural heritage but also plays a role in character formation, strengthening social values, increasing tolerance, and fostering community cultural responsibility.Thus, the implementation of ISBD through the preservation of local culture becomes an important foundation in building a society that is cultured, has character, and has high social awareness amidst changing times. Penelitian ini bertujuan untuk mengkaji relevansi ISBD dalam upaya pelestarian budaya lokal serta peran masyarakat, lembaga pendidikan, dan komunitas sosial dalam menjagakeberlanjutan budaya. Metode penelitian yang digunakan adalahmetode kualitatif dengan pendekatan deskriptif melalui studiliteratur dan observasi sosial terhadap fenomena budaya di masyarakat. Hasil kajian menunjukkan bahwa pelestarianbudaya lokal tidak hanya berfungsi sebagai upaya menjagawarisan budaya, tetapi juga berperan dalam pembentukankarakter, penguatan nilai sosial, peningkatan sikap toleransi, serta penumbuhan tanggung jawab budaya masyarakat. Dengandemikian, implementasi ISBD melalui pelestarian budaya lokalmenjadi fondasi penting dalam membangun masyarakat yang berbudaya, berkarakter, dan memiliki kepedulian sosial yang tinggi di tengah perubahan zaman